Diffusion of Educational Digital Innovation: Implementing The OKY App for Menstrual Education in Junior High Schools - Pulung Siswantara; Muthmainnah Muthmainnah; Mutmainnah Khaerati; Aisyah Amalia; Dini Yulia Restuti; Nurul Indah Qariati; Kurnia Ramadhani (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2026)
Background: Menstruation is a natural phenomenon that occurs in all women. However, it can result in various physical and psychological issues, including elevated stress levels. Inadequate management of menstrual hygiene has been demonstrated to result in reproductive health complications. Recently, the popularity of menstrual tracking applications such as the OKY App has increased, with these applications assisting women in the monitoring of their menstrual cycles. However, it is evident that a significant proportion of adolescents, including those enrolled at State Junior High School (SMPN) 30 Surabaya, have not yet adopted this application. The objective of this study was to analyze the relationship between relative advantage, compatibility, complexity, trialability, observability, and knowledge with the decision and implementation of using the OKY App at SMPN 30 Surabaya.Method: The present research employed a quantitative methodology, adopting a cross-sectional approach and an explanatory research design. The population under study comprised students in 7th and 8th grade at SMPN 30 Surabaya. A simple random sampling technique was used to select 70 respondents. The data was collected via a questionnaire that encompassed a range of variables, including relative advantage, compatibility, complexity, trialability, observability, knowledge, decision, and implementation.Result: The findings indicated that relative advantage exhibited no correlation with the decision-making process concerning the utilization of the OKY App. Complexity was related to the decision to use the app but not to its implementation. Therefore, this variable needs to be considered to ensure the app is more easily accepted by potential users. In conclusion, compatibility, trialability, observability, and knowledge are significantly related to both the decision and implementation of using the OKY App. Relative advantage has no impact on either decision or implementation, while complexity only influences the decision-making process but not the actual use of the app. The findings emphasize the significance of addressing user perceptions and understanding in order to enhance the adoption and sustained utilization of menstrual health technology.